The Effect Of Deceptive Advertising On Consumer Behaviors: A Research Gsm Sector - Çelik, Evren (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2010)
As it is well-known, deceptive advertising has effects on consumer behaviors. This deceptive advertising ads are misleading the consumer perceptions by using demographic characteristics of consumers. They show behavioral differences that have been revealed in various literature researches. The internet and other technological tools can be used to convince the consumers. Young consumers compares competing products or services, investigate them in detail, and then intend to buy them. This research is based on the ways of misleading ads regarding products or services. In other words, research is based on how consumers will create a reaction to the product-related ads giving information. In our research we analyze the young and educated consumer profile, technological monitoring and brand loyalty of people. As it can be noted that products, services and brands ads convince people much easier to give up to texture. Face to face in our work with pre- and post-tests will also support the forming the survey.
Keywords: Ads; Consumer Behaviors; Deceptive Advertising; GSM Sector; Reklamlar; tüketici davranışları; aldatıcı reklam; GSM sektörü